Overview of The Level of Outpatient Satisfaction with Pharmaceutical Services in The Pharmacy Room Jenggawah Sub-District Public Health Jember Regency - Maulina, Novia; Sugihantoro, Hajar; Syahrir, Achmad; Pratiwi, Nurvita Cindy Dwi (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2023)
Health is one of the important things for human life as a supporting factor of the quality of human life. Public health center is the first health facility for the community as an effort to improve health with several health services. One of the health services at the Public health center is pharmaceutical services whose activities are directly responsible for preventing the misuse of drugs against patients by providing the best service so that patient satisfaction arises. The purpose of this research was to determine the level of satisfaction of outpatients with pharmaceutical services in the pharmacy room of the Public health center at Jenggawah sub- district, Jember Regency. This type of research was descriptive research with a quantitative approach. The sampling method uses a nonprobability sampling method with purposive sampling techniques. Samples were obtained 100 respondents. This study refers to service quality (servqual) questionnaire instrument using a Likert scale satisfaction calculation and processed using SPSS 25. The results of the research on the level of patient satisfaction with pharmaceutical services on the pharmacy room's appearance were 78.95% (very satisfied), drug information services 80.33% (very satisfied), The pharmacist hospitality was 84.75% (very satisfied), the speed and accuracy of the officers were 80% (very satisfied), and at the indicators of drug availability 74.25% (medium). So that the majority of outpatient satisfaction with pharmaceutical services in the Pharmacy Room of the Public health center at Jenggawah Sub-district, Jember Regency is in the satisfied category.